A history of sports video games - Lu, Zhouxiang, author.
1 online resource.
Keywords: This book explores the history of sports and sports-themed video games, providing a comprehensive and holistic view of this complex and diverse genre. The author highlights the influence of technological advancement, industry competition and popular culture on game design, marketing strategies and user experience. Offering valuable insights into the historical process of interaction and integration between real-world sport and video games, this volume will enrich existing scholarship on video games. This volume is a valuable contribution to the fields of both game studies and sports studies, and will be perfect for those interested in the history of science and technology as well as social and cultural history.